16: POSTPARTUM DEPRESSION SCREENING IN A PEDIATRIC ED. Issue 3 (March 2016) - Jarvis, L; Badolato, G; Breslin, K; Goyal, M
Abstract : Purpose of Study: Postpartum depression (PPD) occurs in up to 20% of mothers. The American Academy of Pediatrics recommends routine screening for PPD. The pediatric emergency department (PED) serves as a safety-net for vulnerable, high-risk populations, and may be a useful site for screening. This study investigates (1) prevalence of PPD positive screens, (2) factors associated with a positive PPD screen, (3) frequency of mothers who had not completed a PPD screen previously, and (3) acceptability and impact of PPD screening. Methods Used: We performed a prospective, cross-sectional survey of a convenience sample of mothers of infants </=6 months of age presenting with low-acuity complaints. Mothers completed a computerized survey that included a validated PPD screening tool (Edinburgh Postnatal Depression Scale). We calculated frequency of positive screens and performed bivariable logistic regression to identify factors associated with a positive PPD screen. PPD positive-screened mothers were contacted for phone follow-up at one-month. Summary of Results: 121 mothers were screened for PPD (mean age=28± SD 6 years; 86% English vs. Spanish language; 50% non-Hispanic Black race/ethnicity; 75% non-private insurance) during presentation to the ED with their infant (mean age=3±SD 2 months; 51% female). Twenty-seven mothers (22%) screened positive for PPD with eight mothers (7%) reporting suicidal thoughts. Forty-seven percent (57/121) of mothers had never previously been screened, including 59% (16/27) of PPD-positive screened and those endorsing suicidal thoughts (5/8, 63%). Infants of PPD-screened positive mothers had more ED visits than those whose mothers screened negative (median 2 vs. 1). Seventy-four percent (90/121) of participants viewed ED-based PPD screening favorably. At one-month follow-up 100% (n=12) reported ED-based PPD screening acceptable and the majority endorsed positive impact of screening, including increased access to support (8/12, 67%) and improved activities of daily living (10/12, 83%). Conclusions: PPD is reported by approximately 1 in 5 mothers in an urban PED and the majority of PED-screen positive mothers had not been screened previously. PED-based screening was well-accepted and had a positive impact. Our study informs future efforts for interventions to support mothers of young infants who use the PED for care.